The synergistic effect of doxorubicin and ethanolic extracts of Caesalpinia sappan L. wood and Ficus septica Burm. f. leaves on viability, cell cycle progression, and apoptosis induction of MCF7 cells - Sari Haryanti; Suwijiyo Pramono; Retno Murwanti; Edy Meiyanto (Universitas Gadjah Mada, 2016)
Caesalpinia sappan L. and Ficus septica Burm. f known asa potential plant with wide variety of medicinal properties, including anticancer. Present study was aimed to explore cytotoxic effect ofsappan wood (ECS) and awar-awar leaves (EFS), and its combination with doxorubicin (dox) on MCF-7 cells focusing on cell cycle progression and apoptosis induction.The result of MTT assay showed that single treatment of ECS and dox performed cytotoxic effect with the IC50 value of 32 µg/mL and 6 µM respectively, while EFS performed low cytotoxic effect with the IC50 value of 282 µg/mL. The combination of ECS with EFS and doxorubicin showed synergistic cytotoxic effect. Flow cytometry analysis revealed that combination of ECS (16 µg/mL) with EFS (8 µg/mL) and doxorubicin (2 µM) induced apoptosis, and cell accumulation at sub-G1 and G2/M phases.Immunoblotting assay confirmed the apoptosis induction of this combination through increasing of cleavage of PARP-1. Based on these results, the synergistic cytotoxic effect of this combinationwas through G2/M phase accumulation and apoptosis inductionand potentially to be developed as co-chemotherapeutic agent.